The midnight feast : a novel - Foley, Lucy (Novelist) (William Morrow, an imprint of HarperCollinsPublishers, 2024)
It's the opening night of The Manor, and no expense, small or large, has been spared. The infinity pool sparkles; crystal pouches for guests' healing have been placed in the Seaside Cottages and Woodland Hutches; the "Manor Mule" cocktail (grapefruit, ginger, vodka, and a dash of CBD oil) is being poured with a heavy hand. Everyone is wearing linen. But under the burning midsummer sun, darkness stirs. Old friends and enemies circulate among the guests. Just outside the Manor's immaculately kept grounds, an ancient forest bristles with secrets. And the Sunday morning of opening weekend, the local police are called. Something's not right with the guests. There's been a fire. A body's been discovered. THE FOUNDER * THE HUSBAND * THE MYSTERY GUEST * THE KITCHEN HELP It all began with a secret, fifteen years ago. Now the past has crashed the party. And it'll end in murder at... The Midnight Feast.